Peritoneal adhesions. Experimental work: study on the possibility of carrying out a combined pre, per and postoperative treatment of the prophylaxis of peritoneal adhesions - Lesina, Elmer; Pardo, Héctor; Miraglia, Domingo; Pressa, Carlos; Criado, Francisco (Cirugía del Uruguay, 1973)
The authors present an experimental study of the behaviour of deperitonized surfaces sutured, with antiadhesive treatment with Trasylol in dosis of 900.000 I.C.U. distributed during the pre, per and postoperatory periods. Results seem to show the efficiency of this therapeutical procedure in reducing adhesions from 55 % in sutured parietal deperitonizations treated with dosis of up to 300.000 I.C.U. of Trasylol applied exclusively intraperitoneally, to a 16.6 % when thc new procedure is applied.